Dampak Cara Budidaya Ikan Yang Baik (CBIB) Bagi Masyarakat Pembudidaya Terhadap Produksi Budidaya Ikan Air Tawar Di Distrik Muara Tami Kota Jayapura - Vyona Mantayborbir; John Dominggus Kalor; Ervina Indrayani (Cenderawasih University, 2022)
The Good Fish Cultivation Program (CBIB) is an activity that teaches how cultivating good fish to produce good products. in Muara Tami District, Jayapura City, there is still a very low level of knowledge about CBIB, which affects the level of freshwater fish production. The aim of the research is How to Impact the Cultivator Community's Understanding of Good Fish Cultivation Methods on the Production of Freshwater Fish Cultivation in the Muara Tami District, Jayapura City. This study used a qualitative research method, which took place at the People's Hatchery Unit and Fish Farmers Group in Muara Tami District, Jayapura City. This study uses qualitative research methods, with research locations in the community seed units (UPR) and Pokdakan (fish cultivator groups) in Muara Tami District The results showed that the implementation of the CBIB program in the Muara Tami District, Jayapura City, was not optimal. constraints such as, lack of coaching and supervision. From the results of this study it can be concluded that CBIB has not been able to implemented well because it is influenced by 2 aspects: organizational and interpretation aspects, and application aspect. Recommended to the Department of Maritime Affairs and Fisheries of Jayapura City must make efforts to support the fulfillment of the needs of fish cultivators in the Muara Tami District, Jayapura City in terms of organizational and interpretation aspects, and implementation aspects so that the achievement of production and safety and quality can be improved.